Roles of Divalent-Cation Transporter Genes mntB and mntC of Beer Spoilage Bacteria in Resisting Hop Bitter Compound Iso-α-Acid. (4th October 2020) - Zheng, Feiyun; Wang, Tianmu; Niu, Chengtuo; Zheng, Ruilong; Liu, Chunfeng; Wang, Jinjing; Li, Qi
Abstract: This study aimed to address the roles of divalent-cation transporter genes of Lactobacillu s casei 2-9-5 in resisting hop bitter compound iso-α-acid. To determine the underlying mechanisms for Lactobacillus casei strains to resist iso-α-acid, RNA sequencing was performed for La. casei 2-9-5 and W2-9-5, which was an isolate of La. casei W2-9-5 derivative with a relatively weaker iso-α-acid resistance ability, in 0.012% iso-α-acid solution. Results indicated that its resistance of iso-α-acid was closely related to transmembrane transport, membrane composition and oxidative phosphorylation. Compared with La. casei W2-9-5, the expressions of the mntA, mntB and mntC genes were found to be significantly up-regulated in La. casei 2-9-5 and confirmed by RT-qPCR analysis. To examine the roles of these genes, recombinant plasmids harboring these genes were constructed and expressed in model bacteria Lactococcus lactis NZ3900. Relative to controls, the recombinant Lc. lactis containing mntB and mntC genes grew better under iso-α-acid pressure. Furthermore, the intracellular Mn 2+ concentration in La. casei 2-9-5 was much higher than that in La. casei W2-9-5. Together, the data support that manganese transporter genes mntB and mntC are involved in the iso-α-acid resistance ability of La. casei strains through enhancement of intracellular Mn 2+ concentrations.